Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd004943.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions at caesarean section for reducing the risk of aspiration pneumonitis

Abstract: Background Aspiration pneumonitis is a syndrome resulting from the inhalation of gastric contents. The incidence in obstetric anaesthesia has fallen, largely due to improved anaesthetic techniques and the increased use of regional anaesthesia at caesarean section. However, aspiration pneumonitis is still a cause of maternal morbidity and mortality, and it is important to use effective prophylaxis. Objectives To determine whether interventions given prior to caesarean section reduce the risk of aspiration pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…Currently, most cesarean sections are performed under local anesthesia and with appropriate techniques, so the incidence of aspiration pneumonitis syndrome is reduced. [ 18 ] It should be noted that water exits the stomach within 12 min and carbohydrate drinks are not present in the stomach 90 min after drinking. [ 5 ] Ultrasound examination also showed that gastric emptying was normal during pregnancy and decreased only slightly at the onset of labor.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most cesarean sections are performed under local anesthesia and with appropriate techniques, so the incidence of aspiration pneumonitis syndrome is reduced. [ 18 ] It should be noted that water exits the stomach within 12 min and carbohydrate drinks are not present in the stomach 90 min after drinking. [ 5 ] Ultrasound examination also showed that gastric emptying was normal during pregnancy and decreased only slightly at the onset of labor.…”
Section: Discussionmentioning
confidence: 99%
“…The prophylactic use of antacids, H2-receptor antagonists, proton pump inhibitors (PPIs), and prokinetic drugs aims to reduce the volume and increase the pH of gastric contents and minimize the risk of regurgitation and aspiration. A combination of prophylactic agents might be more effective than single medication 37…”
Section: Preoperative Planning and Preparationmentioning
confidence: 99%
“…Metoclopramide 10 mg IV can be used in addition to H2-receptor antagonists or PPIs, but it is more effective as an antiemetic 43. Nonparticulate antacids such as sodium citrate (30 mL) increase gastric pH immediately and for ∼1 hour and therefore should be administered shortly before induction of GA 37,44,45…”
Section: Preoperative Planning and Preparationmentioning
confidence: 99%